BIOSORPTION EVALUATION OF SYNTHETICDYE FROM FOOD INDUSTRY WASTEWATER ONTO SILKWORMCOCOONS: PRELIMINARY STUDIES - DUSI, GIOVANA GONÇALVES; CANTELI, ANDERSON MARCOS DIAS; KARP, JOEL ROBERT; MAFRA, LUCIANA IGARASHI; SCHEER, AGNES DE PAULA; DA SILVA, VITOR RENAN (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2018)
The aim of this study was to evaluate thesynthetic azo dye (tartrazine) biosorption onto second line silkworm cocoons. Batch adsorption system was used to investigate the effect of pH and initial tartrazine concentration in theliquid phase. Also, the kinetic mechanismwas investigated at 20°C and pH 2.0.The highest adsorption was obtained at the lowest pH evaluated, while the assays with pH above 3.0 did not show significant adsorption at the first hour of theprocess, indicating that biosorption is more favorable at lower values ofpH.The adsorption kinetic was studied at pH 2.0andcompared withthe kinetic mechanism ofconvective mass transfer and diffusion models.The kinetic behavior of biosorption process showed a high amount of dye adsorbedat the beginning of the process, however, after saturation of the functional groups, the adsorption rate decreased over time until saturation. After 24 hours of batch operation, the uptake of tartrazine onto silkworm cocoons was 40.39 mg g-1,and the rate of adsorption reduces from 3.430 to 0.003 mg min-1g-1, suggesting that the process approaches the equilibrium. The Crank model provided the best fit. The results revealed that silkworm cocoons have the potential to be used as a biosorbent for wastewater treatment containing tartrazine